The macroeconomic effects of fiscal policy in Portugal : a Bayesian SVAR analysis - Afonso, António (2010)
In the last twenty years Portugal struggled to keep public finances under control, notably in containing primary spending. We use a new quarterly dataset covering 1979:1-2007:4, and estimate a Bayesian Structural Autoregression model to analyze the macroeconomic effects of fiscal policy. The results show that positive government spending shocks, in general, have a negative effect on real GDP; lead to important "crowding-out" effects, by impacting negatively on private consumption and investment; and have a persistent and positive effect on the price level and the average cost of financing government debt. Positive government revenue shocks tend to have a negative impact on GDP; and lead to a fall in the price level. The evidence also shows the importance of explicitly considering the government debt dynamics in the model. Finally, a VAR counter-factual exercise confirms that unexpected positive government spending shocks lead to important "crowding-out" effects.